Emergency Medical Services and Primary Health Care linkage: a potential solution for effective emergency response in rural areas: the case of Ukraine - Castro-Delgado, Rafael; Panta Bhandari, Manisha; Subedi Acharya, Radha (Frontiers in Public Health, 2025)
Ukraine’s emergency medical system faces significant challenges, particularly in rural and conflict-affected areas, where gaps in coordination, infrastructure, and access to care persist. Despite investments and reforms, the fragmentation between Emergency Medical Services (EMS) and Primary Health Care (PHC) has limited the effectiveness of emergency response, especially in rural areas. This viewpoint proposes the integration of EMS and PHC as a strategic solution to enhance response capacity, reduce delays, and improve health outcomes in rural populations. Drawing on the successful model from the Asturias region in Spain, an example of PHC network for WHO and where PHC is embedded in emergency response pathways, the article outlines a feasible roadmap for Ukraine that may be followed by other countries to improve emergency response in rural areas. Key elements include the establishment of joint protocols, integrated communication systems, standardized referral pathways, and targeted personnel training. Following European Union regulations, the adoption of a single emergency number (112) is also discussed as a critical step toward improved interagency coordination. By aligning PHC infrastructure with EMS operations, Ukraine can strengthen its emergency care system and ensure equitable access to timely medical interventions across its territory.